The Moderating Effect of Trade Openness on the Relationship between Public Expenditure and Economic Security - Kairu, Wamagata; Elly, Duncan; Ochieng, Herick (European Journal of Business and Strategic Management, 2025)
Purpose: The objective of this study was to find out the relationship between public expenditure and economic security and find out whether the relationship between public expenditure and economic security is moderated by trade openness. Methodology: The study used positivism research philosophy and adopted the descriptive and exploratory study designs in analyzing the longitudinal and cross-sectional panel data to describe and evaluate the relationship between public expenditure and economic security and examine whether trade openness had moderating influence on the relationship between public expenditure and economic security among the five selected EAC member countries that were Kenya, Uganda, Tanzania, Burundi and Rwanda. The study used secondary panel data, from year 2008 to 2022, that was sourced from the World Bank Development Indicators, for five selected countries of the East African Community. The study adopted the Broyden–Fletcher–Goldfarb–Shanno Autoregressive Moving Average Generalized Least Squares regression model to test the research hypotheses. Findings: The study found that public expenditure had statistically significant effect on economic security. The study further found that trade openness had positive statistically insignificant moderating influence on the relationship between public expenditure and economic security with strengthening trade openness reducing the adverse effect that public expenditure has on economic security. Unique Contribution to Theory, Practice and Policy: The study findings have contributed to new knowledge on the connection between public expenditure and economic security where public spending was shown to have a significant adverse effect on economic security. The study findings also contributed to the growing knowledge on construction and composition of economic security indices, which factors various parameters. The study findings can guide policy makers to develop trade policies that would balance between economic nationalism and trade openness in a manner to harness the favorable effect that trade openness has in weakening the adverse influence of public expenditure on economic security.